Solve for y 8y+6=9y

Math
8y+6=9y
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 9y from both sides of the equation.
8y+6-9y=0
Subtract 9y from 8y.
-y+6=0
-y+6=0
Subtract 6 from both sides of the equation.
-y=-6
Multiply each term in -y=-6 by -1
Tap for more steps…
Multiply each term in -y=-6 by -1.
(-y)⋅-1=(-6)⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=(-6)⋅-1
Multiply y by 1.
y=(-6)⋅-1
y=(-6)⋅-1
Multiply -6 by -1.
y=6
y=6
Solve for y 8y+6=9y

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top